Dampak Implementasi Program Rumah Tidak Layak Huni (RTLH) Pada Rakyat Penerima Manfaat : (Studi Di Kecamatan Rowosari Kabupaten Kendal) - Tri Lestari Hadiati; Hidayat Hidayat (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
In the 1945 Constitution Article 28 H of Amendment IV, it is stated that "Home is one of the basic rights of every citizen, so every citizen has the right to a place to live and a healthy living environment". Observing this, the people have the right to own their own homes. The fact is that realizing a livable home is not easy, for most poor people. This is also the case in Rowosari Sub-district, Kendal Regency, where in the last three years (2021-2023) a number of poor people who live in uninhabitable houses have received financial assistance from the RTLH Program. The purpose of this study is to analyze the impact of the RTLH Program Implementation on the poor beneficiaries. The type of research used is complementary descriptive research, the population is all poor beneficiaries in 2023 totaling 40 people. The sampling technique is with the census technique, the data collection is by observation, interview, questionnaire & documentation. The data analysis technique uses descriptive qualitative methods with percentages.Based on the study of Edward III Implementation Theory & Evaluation Theory, the implementation of the RTLH Program for 40 families in Rowosari Sub-district had a very good impact (above 75%). Although some other recipients said the impact was only good (65%-74.99%). However, a small proportion (2.5%-12.5%) said that the impact was quite small for them, because they had high expectations, tending to expect total assistance, to improve their lives.